A postoperative brain abscess due to Propionibacterium acnes in an immunocompetent adult with incidental discovery. (September 2022) - Borni, Mehdi; Abdelmouleh, Souhir; Mechergui, Haifa; Elouni, Emna; Boudawara, Mohamed Zaher
Abstract: Introduction: and importance: Propionibacterium acnes (P. acnes) is an anaerobic, lipophilic, Gram-positive bacteria of the commensal skin flora. It may also be present on the mouth's mucosa, nose, urogenital tract, and large bowel. P. acnes is an unusual and rare agent of intracerebral abscess although in recent years some publications suggest that its frequency in brain surgery is increasing. Case presentation: The authors report a case of an incidental cerebral abscess during follow-up imaging in a 63-year-old male patient operated on twice for cerebral meningioma the last of which was 3 months ago without placement of any surgical implant with uneventful postoperative course. Clinical discussion: P. acnes is still an sunder-appreciated cause of post-neurosurgical infection. Time between neurosurgery and infection is variable ranging from few months to many years. Its culture time is long, with currently an average time to positivity of six days (2–15 days), justifying prolonged cultures. Conclusion: Intracranial infections by P. acnes are not quite frequent. We emphasize the need to send samples for culture of anaerobes in this type of complications before giving a negative result. Highlights: Propionibacterium acnes (P. acnes) is an anaerobic, lipophilic, Gram-positive bacteria belonging to the Propionibacterium spp family. It is a bacterium of the commensal skin flora, where it colonizes the hair follicles and the sebaceous glands. P. acnes is an unusual and rare agent of intracerebral abscess, although in recent years some publications suggest that its frequency in brain surgery is increasing. Culture time is long, with currently an average time to positivity of six days (2–15 days), justifying prolonged cultures. Concerning the principles of treatment, it is uncommon to be certain of the diagnosis of P. acnes infection. This current case is an addition to the literature which remains rare demonstrating that this bacterium is able to cause CNS damage in immunocompetent subjects and must be taken into account in the differential for the cause of intracranial suppuration.